Association of Chlamydia trachomatis, Neisseria gonorrhoeae, Mycoplasma genitalium and Ureaplasma species infection and organism load with cervicitis in north Indian population. (10th August 2021) - Roy, A.; Dadwal, R.; Yadav, R.; Singh, P.; Krishnamoorthi, S.; Dasgupta, A.; Chakraborti, A.; Sethi, S.
Abstract: Cervicitis is predominantly caused by Neisseria gonorrhoeae and Chlamydia trachomatis, which accounts for almost half of all the cases of cervicitis. The role of newer organisms like Mycoplasma genitalium and Ureaplasma sp. and association of bacterial load with cervicitis are also not well established. So the study aimed to determine the relative frequency of these organisms and their load in association with cervicitis cases from north India. A case–control study involving 300 women was conducted using quantitative real‐time PCR from endocervical swabs for identification of organisms and quantification of bacterial load. Among 150 cervicitis cases, C. trachomatis, N. gonorrhoeae, M. genitalium and Ureaplasma parvum were detected in 5 (3·3%), 10 (6·6%), 37(24·6%) and 47 (31·3%) respectively. Old age (<0·001, chi‐squared test) and irregular menstrual cycles (<0·001, chi‐squared test) were significantly associated with cervicitis. M genitalium was the only organism to be associated significantly with cervicitis with regard to age (<0·031) and symptoms like discharge ( P < 0·033, chi‐squared test) and dysuria ( P < 0·044, chi‐squared test) in multivariate analysis. Our finding suggests that the bacterial load of these organisms is not significantly associated with cervicitis. However, we found significant association of M. genitalium infection with clinical characteristics of cervicitis cases. Abstract : Significance and Impact of the Study: Our study addresses the need of diagnosis‐based treatment of the potential sexually transmitted infections as it demonstrates that the clinical diagnosis of cervicitis is a poor predictor of Chlamydia trachomatis, Neisseria gonorrhoeae or Mycoplasma genitalium infection. Thus, the syndromic approach of treatment should be replaced with diagnosis‐based treatment to prevent the unnecessary administration of the drugs and prevent development of drug‐resistant organisms.